The term structure of interest rates : financial intermediaries and debt management - Michaelsen, Jacob B. (New York : Intext Educational Publishers, 1973)
This book is intended for use in a variety of undergraduate courses in Money and Banking. It is also useful supplementary reading in courses on macroeconomics and financial markets.
Includes index.
Includes bibliographical references: p. 164-168.
ne 21/01/2019
Loans
Keywords: Interest rates; Investments; Financial institutions